Induced selectivity in the photochemistry of estrone derivatives in sustainable and micellar environment: preparative and mechanistic studies - Quindt, Matías Iván (2021)
In this study, we carried out preparative and mechanistic studies on the photochemical reaction of a series of 3-acylestrone derivatives in confined and sustainable micellar environment under steady-state conditions and the results were compared with those obtained in cyclohexane solution. Theaim of this work is mainly focused to show whether the nature of the surfactant (cationic, neutral and anionic) leads to noticeable selectivity in the photoproduct formation. The 3-acylestrone derivatives underwent the photo-Fries rearrangement, with concomitant homolytic fragmentation of the ester group and [1;3]-acyl migration. This pathway afforded the ortho-acyl estrone derivatives, the main photoproducts together with estrone. However, epimerization of the ortho regioisomer 2-acetylestrone and estrone through Norrish Type I photoreaction occurred involving the fragmentation of the C-alpha at the carbonyl group (C-17) of the steroid. UV-visible and 2D-NMR (NOESY) spectroscopies have been employed to measure the binding constant Kb and the location of the steroids within the hydrophobic core of the micelle.